Morphologic and Surface Characterization of Different Types of Activated Carbon Fibres - Jo Anne G. Balanay; Claudiu T. Lungu (Adsorption Science & Technology)
This study provides a comparison of different types of commercially available activated carbon fibres (ACFs). Thus, ACFs in cloth (ACFC) and felt forms (ACFF) with three different surface areas were each analyzed for their pore volumes, pore sizes and pore-size distributions. The fibre morphology and organization was visualized using scanning electron microscopy (SEM). The microporosity of the ACF materials based on nitrogen isotherms, the percentage of micropores by area and volume, the average pore size and the pore-size distribution were also determined. An increase in the surface areas of the ACFC types led to an increase in the total pore volume, micropore volume, micropore area and pore width, but led to a decrease in the percentage of micropores by area and volume. The nitrogen isotherms demonstrated that the surface area dictated the amount of adsorption onto the ACF regardless of the form of the latter. The difference in the volume of smaller micropores between the ACFC and ACFF types may be attributed to the difference in the adsorbent density and the accessibility of the fibre surface to the activating gas during the activation process. An understanding of the pore structure of ACFs by form and surface area is crucial in determining the appropriate specific applications of such adsorbents.